2021
DOI: 10.3389/ffgc.2021.701293
|View full text |Cite
|
Sign up to set email alerts
|

Stemflow Infiltration Hotspots Create Soil Microsites Near Tree Stems in an Unmanaged Mixed Beech Forest

Abstract: In stemflow, rainfall is collected and channeled to a concentrated soil water input. It can constitute up to 30% of incident precipitation in some ecosystems. However, the size of the zone influenced by stemflow is unclear, and statistically representative measurement of stemflow (on and in between sites) is scarce. Therefore, whether stemflow creates hotspots of infiltration and potential impacts on forest soils remain subject to controversy. In this study, we investigated the areal dimension of infiltrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 66 publications
(205 reference statements)
2
26
0
Order By: Relevance
“…In the solid soil phase, our investigations found no evidence of this effect with regard to soil pH and base saturation. This confirms the results by (Metzger et al, 2021) from a mixed European beech forest, who also found no pH differences and attributed this to low air pollution. Our study site is also located in an area with relatively low atmospheric deposition (Wellbrock et al, 2005), as indicated by similar pH values in SF, TF and PR (Supplement 1).…”
Section: Chemical Soil Conditionsupporting
confidence: 91%
“…In the solid soil phase, our investigations found no evidence of this effect with regard to soil pH and base saturation. This confirms the results by (Metzger et al, 2021) from a mixed European beech forest, who also found no pH differences and attributed this to low air pollution. Our study site is also located in an area with relatively low atmospheric deposition (Wellbrock et al, 2005), as indicated by similar pH values in SF, TF and PR (Supplement 1).…”
Section: Chemical Soil Conditionsupporting
confidence: 91%
“…Recently, in German temperate forests, Metzger et al . ( 2021 ) found near‐stem microsites of unique physiochemistry, including increased soil organic C content and macropore proportion, and Jochheim et al . ( 2022 ) found higher macronutrient ion and heavy metal concentrations in soil solutions within the stemflow infiltration area.…”
Section: Discussion Of Stemflow Influences Over Soil Bacterial Commun...mentioning
confidence: 96%
“…The significant influence of stemflow on soil moisture, physiochemistry and the composition of soil solutions has been reported for trees generating similar amounts of stemflow as observed at our site. Recently, in German temperate forests, Metzger et al (2021) found near-stem microsites of unique physiochemistry, including increased soil organic C content and macropore proportion, and Jochheim et al (2022) found higher macronutrient ion and heavy metal concentrations in soil solutions within the stemflow infiltration area. At a forest site on the Canary Islands, Aboal et al (2015) studied a range of tree species with differing stemflow generation, finding multiple soil chemical variables, pH, conductivity, and available phosphorus, correlated with the corresponding tree's stemflow inputs.…”
Section: Discussion Of Stemflow Influences Over Soil Bacterial Commun...mentioning
confidence: 99%
“…Considering that the topsoils near our studied trees have a mean clay content greater than 15%, there is a high probability of having macropore structures and consequently preferential flow in the forest soils of our study. Metzger et al (2021) found that soil microsites near tree stems had lower field capacity and higher hydraulic conductivities, which indicated increased macroporosity near tree stems. In addition, tree root systems, both dead and alive, allow the funnelling of stemflow water as preferential flow, bypassing the soil matrix (e.g., Johnson & Lehmann, 2006; Liang et al, 2011; Martinez‐Meza & Whitford, 1996; Schwärzel et al, 2012; Spencer & van Meerveld, 2016).…”
Section: Discussionmentioning
confidence: 99%